Physical Chemistry of Curvature and Curvature Stress in Membranes - G. Mouritsen, Ole (Current Physical Chemistry, 2013)
The lamellar lipid-bilayer component of cell membranes is a complex self-assembled macromolecular aggregate that hosts a large part of the cell's biological activity such as signal transduction, energy- and materials transport, as well as communication with the environment. The structure, dynamics, and stability of the lipid bilayer are controlled by thermodynamic forces leading to overall tensionless bilayers with a conspicuous lateral pressure profile and build-in curvature-stress instabilities that may be released locally or globally in terms of morphological changes leading to the formation of non-lamellar and curved structures. A key controller of the bilayer's propensity for forming curved structures is the average molecular shape of the different lipid molecules. The molecular shape mediates, via the curvature stress, a coupling to membrane-protein function. The present mini-review provides a status of the field with a focus on how curvature and curvature stress as an emergent property of a macromolecular assembly may furnish an understanding of biological activity at membranes. An example is given of how this insight can be transferred into technology.
Keywords: Lipid molecular shape